![9(3x+6)=-12+5x](https://img.qammunity.org/2023/formulas/mathematics/college/ause83nxxqprrqxhi6iqicl09wum5vyhxh.png)
To find the value of x in the equation above, here are the steps.
1. Distribute 9 to the numbers inside the parenthesis.
![\begin{gathered} 9(3x)+9(6)=-12+5x \\ 27x+54=-12+5x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ggq1foseikh0vrc33prl5pn3ajlkrj3gdz.png)
2. Transfer 5x to the left side reversing the sign. Transfer 54 to the right side reversing the sign as well.
![\begin{gathered} 27x-5x=-12-54 \\ 22x=-66 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j088xzcuhiet2hrbdvalyezokz4447mw4s.png)
3. Divide both sides by 22.
![\begin{gathered} (22x)/(22)=-(66)/(22) \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qekvcltvdk1q3i8wjp4y8u32gqvdmt5jri.png)
Therefore, the value of x = -3.
To doublecheck if that is correct, let's replace x with -3 in the original equation.
![\begin{gathered} 9(3(-3)+6=-12+5(-3) \\ 9(-9+6)=-12-15 \\ 9(-3)=-27 \\ -27=-27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tbiz60ar4evzbeg0yk53z6uxp17xjj68wa.png)
Indeed, at x = -3, both sides are equal to each other that is -27.